2007
DOI: 10.1302/0301-620x.89b7.18593
|View full text |Cite
|
Sign up to set email alerts
|

What impact have NICE guidelines had on the trends of hip arthroplasty since their publication?

Abstract: The National Institute for Clinical Excellence (NICE) published the guidelines on the selection of prostheses for primary hip replacement in 2000. They supported the use of cemented hip prostheses to the exclusion of uncemented and hybrid implants. The information from the Trent (and Wales) Regional Arthroplasty Study has been examined to identify retrospectively the types of hip prostheses used between 1990 and 2005, and to assess the impact that the guidelines have had on orthopaedic practice. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…One recent study, for example, shows that 86.4% of obstetric units the UK study exceeded the maximum dose of intravaginal prostagland used to induce labour recommended by NICE [38]. Roberts et al [39] found that cemented hip prostheses fell between 2001 and 2005-that is after NICE guidance supporting use of cemented prosthesis in 2000. Over the same period the use of hybrid prosthesis more than doubled (from 8.8% to 22%), in contravention of the NICE guidance.…”
Section: The Impact Of Guidelines On Practicementioning
confidence: 99%
“…One recent study, for example, shows that 86.4% of obstetric units the UK study exceeded the maximum dose of intravaginal prostagland used to induce labour recommended by NICE [38]. Roberts et al [39] found that cemented hip prostheses fell between 2001 and 2005-that is after NICE guidance supporting use of cemented prosthesis in 2000. Over the same period the use of hybrid prosthesis more than doubled (from 8.8% to 22%), in contravention of the NICE guidance.…”
Section: The Impact Of Guidelines On Practicementioning
confidence: 99%
“…For example, a population-based assessment of performance on 439 recommendations for 30 conditions spanning preventive, acute, and chronic care services found that only 55% of patients in the United States received recommended care (18). In addition, the lack of adherence to practice guidelines continues to be identified worldwide across different conditions and settings of care (19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Indeed the NHS has an obligation to implement NICE technology assessments within three months of publication [3] . However, uptake of new guidance can be suboptimal [4] , [5] , [6] , [7] , [8] , [9] . For example, heat maps for the use of medical technologies and primary care medicines show that there is wide variation between the medicines patients can access in one part of England compared with other parts [4] .…”
Section: Introductionmentioning
confidence: 99%